2001
DOI: 10.1093/bja/87.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal ropivacaine for total hip arthroplasty: double-blind comparative study with isobaric 7.5 mg ml −1 and 10 mg ml −1 solutions

Abstract: This study was designed to evaluate the efficacy and safety of two concentrations of intrathecal ropivacaine, 7.5 and 10 mg ml(-1), in patients undergoing total hip arthroplasty. One hundred and four patients, ASA I-III, were randomized to receive an intrathecal injection of one of two concentrations of isobaric ropivacaine. Group 1 (n=51) received 2.5 ml of 7.5 mg ml(-1) ropivacaine (18.75 mg). Group 2 (n=53) received 2.5 ml of 10 mg ml(-1) ropivacaine (25 mg). The onset and offset of sensory block at dermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
39
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 13 publications
12
39
3
1
Order By: Relevance
“…Tramadol. Our study was in accordance with various studies, [16,17] who also found insignificant changes with respect to nausea and vomiting. There was no case of local anaesthetic toxicity, pruritus or total spinal in both the groups.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Tramadol. Our study was in accordance with various studies, [16,17] who also found insignificant changes with respect to nausea and vomiting. There was no case of local anaesthetic toxicity, pruritus or total spinal in both the groups.…”
Section: Discussionsupporting
confidence: 94%
“…In terms of safety, both doses of intrathecal ropivacaine provided high degree of cardiovascular stability with a low incidence of bradycardia and hypotension. The results correspond with other studies, [16,17,18] in which it was found that there was high degree of cardiovascular safety and there was no difference in various groups receiving different doses of ropivacaine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were similar to studies of McNamee et al and Van Kleef et al with regards to time taken to achieve maximum motor block and duration of motor block [9], [10] . Result of this study also coincide with Gonul Sagiroglu et al as in their study the isobaric ropivacaine group showed a more rapid recovery from motor block compared with the ropivacaineclonidine groups [7] .…”
Section: Discussionsupporting
confidence: 92%
“…30 The choice of a 12 mg dose for the 0.4% ropivacaine group was in accordance with results of different dose-finding studies. 22,31,32 For prilocaine, the dose of 60 mg was chosen in accordance with the results of a study by Camponovo et al Their study results showed that 13% of patients receiving 40 mg of intrathecal hyperbaric 2% prilocaine and none of the patients receiving 60 mg of plain prilocaine needed supplementary analgesics prior to the end of surgery. 33 The discharge time of patients in the plain ropivacaine group was in accordance with other studies comparing plain ropivacaine with hyperbaric ropivacaine at doses up to 15 mg. [34][35][36][37] Nevertheless, it is difficult to compare sensory or motor recovery due to a number of differences between the various studies, including study design, injection techniques (median, paramedian, slow injection, needle orifice facing up or toward the patient's head/toe), 11,33 needles (25-27G), 33,38 location of lumbar space (L1/L2 -L4/L5), 38,39 patient management after injection (immediate turning to supine position or remaining in the lateral position for a longer period), [38][39][40] and motor scales (Bromage, modified Bromage scale).…”
Section: Discussionmentioning
confidence: 99%